(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
The proposed system is very helpful for blind people, in term of taking an idea about the attendance person/s in their environment simultaneously, so an assistive system based on raspberry pi3 is developed to inform the blind how many persons are around. This work focuses on face detection based on Haar cascade algorithm and OpenCV using python. Satisfied results with different cases are obtained with high accuracy and short processing time, hence OpenCV reduce the delay for getting output, and Haar cascade algorithm increases the accuracy, the system is portable and very light to carry.